Optimization of training for muscle hypertrophy and its implication into gymnastics - Kolar, J.; Podlogar, T. (International Scientific Congress Slovenian Gymnastics Federation, 2017)
Training for muscle hypertrophy has received a lot of scientific and public attention recently. This article summarizes current body of literature regarding optimization of muscle hypertrophy by manipulating different training variables such as intensity, volume, exercise selection, rest interval, muscle failure and repetition speed, which are thought to be the major determinants of muscle growth. As muscle hypertrophy is not always a desired outcome of strength training as could be the case in gymnastics where increased body weight might hamper performance, this article also provides recommendations for gymnasts on how to plan strength training to improve abilities such as muscle power or endurance.